Dyslipidemia and hyperglycemia in patients with acanthosis nigricans: A descriptive cross-sectional study - Regmi, Garima; Aryal, Eliz; Shrestha, Prasanna Raj (Grande Medical Journal, 2025)
Background Acanthosis nigricans is a common dermatosis that typically involves the neck and intertriginous areas of the body. It is usually associated with obesity, dyslipidemia, diabetes mellitus, and insulin resistance. Studies on acanthosis nigricans from Nepal are limited. Method This cross-sectional descriptive study was conducted to assess the prevalence of dyslipidemia and hyperglycemia in patients diagnosed with acanthosis nigricans at a tertiary care hospital from March 2023 to March 2024, following approval of the ethics committee. The diagnosis of acanthosis nigricans was made by a consultant dermatologist. Histopathological confirmation was performed when the diagnosis was uncertain. Demographic data, clinical history, fasting blood glucose, and fasting lipid profiles were collected from 78 consenting patients. Result The mean age of the participants was 31±9 years, with a slight male preponderance (59%). All the patients were from Bagmati province. Dyslipidemia was found in 40 patients (51.28%), among whom 20 had hypercholesterolemia, 13 had hypertriglyceridemia, and 7 had both. Hyperglycemia was identified in 17.95% of the patients. Both dyslipidemia and hyperglycemia were found in 10.25% of the patients. In total, 79.48% of the patients had at least one of the two metabolic problems. Conclusion A high prevalence of dyslipidemia and hyperglycemia was observed in patients with acanthosis nigricans. These findings underscore the need for comprehensive evaluation and management beyond dermatological treatment.